Disclosure rules, controlling shareholders, and trading activity in the new issues market - Samdani, Taufique (Journal of Banking & Finance, 2024)
This study examines the impact of controlling shareholders’ ownership on trading activity under regimes with different disclosure rules. In regimes with ambiguous disclosure rules, trading volume and turnover are higher when controlling shareholders’ ownership is low and their control rights potentially exceed their cash flow rights. However, this impact diminishes in regimes with strict and unambiguous disclosure rules. These findings are robust to endogeneity concerns, suggesting that investor beliefs about potential agency conflicts are less heterogeneous, as evidenced by their trading behavior when disclosure rules are stringent and well defined. The results highlight the role of disclosure credibility and readability in influencing trading activity, offering new insights into the relationship between ownership structure and market behavior.